2020
DOI: 10.1155/2020/9816942
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Natural Convection Viscoelastic Jeffrey’s Nanofluid Flow from a Vertical Permeable Flat Plate with Heat Generation, Thermal Radiation, and Chemical Reaction

Abstract: The boundary layer flow of an incompressible viscoelastic Jeffrey’s nanofluid from a vertical permeable flat plate is investigated. We consider the effects of heat generation, thermal radiation, and chemical reaction on the fluid flow. The nonlinear transformed coupled differential equations that describe the transport processes are solved numerically using a multidomain bivariate spectral quasilinearization method (MD-BSQLM). This innovative method involves blending the quasilinearization idea with the bivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Agbaje TM et al [5] Researched natural convection viscoelastic Jeffrey's nanofluid flow from a vertical permeable flat plate with heat generation, thermal radiation and chemical reaction. The findings depicted that Debora number and suction parameter had related effects on the velocity profile.…”
Section: Introductionmentioning
confidence: 99%
“…Agbaje TM et al [5] Researched natural convection viscoelastic Jeffrey's nanofluid flow from a vertical permeable flat plate with heat generation, thermal radiation and chemical reaction. The findings depicted that Debora number and suction parameter had related effects on the velocity profile.…”
Section: Introductionmentioning
confidence: 99%
“…This happens because the more significant the magnetic variation, the more nanoparticles increase. The effect of heat generation and thermal radiation on nanofluids flow was used in [7], [8]. Maxwell nanofluid flow with Copper (Cu) and Titanium (Ti) nanoparticles were carried out [9], and it was found that the volume fraction affects the fluid temperature.…”
Section: Introductionmentioning
confidence: 99%